Queer TV China : Televisual and Fannish Imaginaries of Gender, Sexuality, and Chineseness - Zhao, Jamie J. (Book collections on Project MUSE., 2023)
The 2010s have seen an explosion in popularity of Chinese television featuring same-sex intimacies, LGBTQ-identified celebrities, and explicitly homoerotic storylines even as state regulations on 'vulgar' and 'immoral' content grow more prominent. This emerging 'queer TV China' culture has generated diverse, cyber, and transcultural queer fan communities. Yet these seemingly progressive televisual productions and practices are caught between multilayered sociocultural and political-economic forces and interests. Taking 'queer' as a verb, an adjective, and a noun, this volume counters the Western-centric conception of homosexuality as the only way to understand nonnormative identities and same-sex desire in the Chinese and Sinophone worlds.